The Synthesis of Theater and Poetic Art in the S.A. Yesenin’s Dramatic Poem “Pugachev” - Alla A. Nikolaeva (Studia Litterarum)
Yesenin’s innovation as a playwright was clearly manifested in the fact that he combined the features of poetic and theatrical art in a dramatiс poem “Pugachev,” putting forward the idea of the supremacy of the sounding word. The combination of philological and theatrical approaches in the analysis of the work shows that the word in Yesenin’s drama includes all the main means of theatrical expressiveness. The monologues of the heroes of the poem contain decorations, light and sound effects; the words of the participants in the action characterize the peculiarities of the mise-en-scenes. All these theatrical effects are created exclusively by poetic means. This confirms the idea of the synthesis of theatrical and poetic art in the poem, reveals the concept of “theater of the word” and the stage potential of the work in a new way. The article concludes that Yesenin is the playwright, who is well acquainted with the theatrical searches and experiments of his time, when the director’s reading of the play and the expressive possibilities of its stage implementation came to the fore. Yesenin is the “director of the word.”